Impacts of COVID-19 on SDGs implementation and service delivery in South Africa - Nhamo, Godwell; Chapungu, Lazarus (Frontiers in Sustainability, 2024)
As the world races towards the 2030 deadline on Sustainable Development Goals (SDGs) implementation, the COVID-19 pandemic posed significant setbacks on progress, particularly at local levels. This paper examines COVID-19's disruption of the implementation of SDGs and service delivery in South Africa, with a focus on Limpopo Province. The study focuses on perceptions from government employees (n = 191), households (n = 4,564), civil society organizations (n = 143), and agricultural communities (n = 68). Results show uneven impact of the pandemic across different SDGs. While all SDGs, except SDG14 (Life Below Water), were affected, six goals were especially hard hit: SDG1 (No Poverty), SDG2 (Zero Hunger), SDG3 (Good Health and Wellbeing), SDG4 (Quality Education), SDG8 (Decent Work), and SDG12 (Responsible Consumption and Production). The Limpopo Province, which grapples with high levels of poverty, unemployment, and inequality, faces additional hurdles in regaining its momentum toward SDG attainment. The study observes an urgent need for targeted interventions, revised strategies, and enhanced monitoring frameworks to ensure that the province, and South Africa at large, can make meaningful progress in the remaining years toward the 2030 Agenda. The work also reveals that without deliberate and scaled-up efforts, the province's path to sustainable development remains out of reach, exacerbating existing inequalities and development challenges.